Illustration of econometric techniques: Analysis and prediction of the industrial sector - Salinas Ortiz, José (2022)
This article describes and discusses the fundamental concepts of Econometric Analysis using a concrete application that allows illustrating the proper use of econometric techniques to econometrics students, and in general to people interested in using these techniques. The estimation period of the application covers 16 years, in which the author uses the aforementioned techniques to analyze the behavior of the manufacturing sector. To illustrate the concepts and use of econometrics in estimation and analysis, the “Stepswise” technique is used, which allows presenting the different statistics that indicate the degree of success achieved with each of the estimated equations, and the main problems of the analysis regression (multicollinearity, autocorrelation). In addition, criteria are presented to choose the best among the estimated equations. Finally, it is emphasized that the researcher must complement the econometric techniques with his theoretical knowledge and his experience or understanding of the phenomenon he seeks to explain.